2015
DOI: 10.2106/jbjs.n.01221
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Preserving the Radial Tuberosity During Distal Biceps Repair

Abstract: The anterior protuberance of the radial tuberosity functions as a supination cam; therefore, consideration should be given to preserve its topographical anatomy during a distal biceps repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
2
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 47 publications
0
36
2
8
Order By: Relevance
“…Schmidt et al, 9 in an anatomical and biomechanical study, showed that sparing the radial bicipital tuberosity has a cam effect on supination strength; the anatomical site of distal reattachment of the biceps brachii is ulnar to such tuberosity. In cadavers, the anatomical reattachment had the same biomechanical results as the intact tendon regarding supination; the worst results were obtained when reattachment was radial to the tuberosity, which is deemed non-anatomical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmidt et al, 9 in an anatomical and biomechanical study, showed that sparing the radial bicipital tuberosity has a cam effect on supination strength; the anatomical site of distal reattachment of the biceps brachii is ulnar to such tuberosity. In cadavers, the anatomical reattachment had the same biomechanical results as the intact tendon regarding supination; the worst results were obtained when reattachment was radial to the tuberosity, which is deemed non-anatomical.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanically, the biceps is considered the primary supinator of the forearm and a secondary elbow flexor. [7][8][9][10][11] As such, surgical repair with anatomical reinsertion of the DBBT in the radial tuberosity is indicated for athletes, active patients with high demand, and those who do not accept permanent functional deficits or esthetic deformity. [11][12][13][14] There are several surgical techniques for the repair of DBBT rupture; the first of them is through a single anterior incision across the elbow.…”
Section: Introductionmentioning
confidence: 99%
“…La tuberosidad radial presenta una protuberancia justo anterior a la inserción del tendón que produce un fenómeno de leva por rotación, aumentando la distancia del centro del radio a la inserción del tendón, que aumenta la ventaja mecánica del mismo. La violación de dicha protuberancia disminuye la ventaja biomecánica, traducida en una pérdida de la fuerza normal de supinación (10) . La realización de una trinchera para la introducción del tendón disminuiría la ventaja de la leva y podría no ser el mejor método de reconstrucción para preservar la fuerza de supinación.…”
Section: Anatomía Y Conceptos Biomecánicos Del Tendón Y La Tuberosidaunclassified
“…Habitualmente, la colocación de los implantes se encuentra en mayor anteversión a la huella anatómica y, en los casos en los que se realiza un fresado para la colocación de un tornillo interferencial, el riesgo de fractura obliga a centrarse en el radio. De cualquiera de las dos formas, se pierde el efecto de leva y estos pacientes pueden no recuperar la fuerza de supinación completamente (10) . Existen técnicas descritas desde una incisión anterior para lograr una inserción anatómica: en una de ellas se incluyen 2 perforaciones de anterior a posterior y colocando un mosquito curvo en la cara dorsal se recuperan las suturas (que se pasan de anterior a posterior) y se captura el tendón con las suturas y, al traccionar de las mismas por las hebras que salen por la cortical anterior del radio, se tensan y se anudan sobre el puente óseo en la cortical anterior (SPOC) (10,53) .…”
Section: Técnica De Incisión Anterior úNicaunclassified
“…Anatomic repair is reported to be more reliable in recreating the supination strength [26] by preserving the ulna position of the tendon footprint on the radial tuberosity and thus restoring the supination 'cam' (Figure 1). Our study only subjectively measured supination strength and thus no accurate conclusions can be drawn on this point; this is a weakness of the study.…”
Section: Figure 2 Table Of Comparative Studies Of Re-rupture Rate Andmentioning
confidence: 99%